Cultural theme of Mother´s Presence in Bader Al Sayab Poetry (Position absence \ Margin Presence) - Al Shorofat, Abdallah Ayed (Journal of Humanities & Social Sciences, 2020)
This research aims at exploring the consistency the implied meaning in modern Arabic poetry and the social and political circumstances and patterns of life prevailing in the Arab society, which appear in special, non-public blogs related to the mother of one of the greatest poets of the modern era, Bader Al Sayab, who enjoys a clear presence in the poetic arena.His poetry can form notification blogs with its clear conditions that prove the consistency the implied meaning and be a sample of the representations of the mother image in Arabic poetry and present the remarkable presence of the mother. His poetry, with its characteristics, can be fertile ground for this analytical reading form on which the research is based.
Keywords: cultural criticism; format; modern Arabic poetry; center and margin